Rentier Islamism: Muslim Brotherhood affiliates in Kuwait, Qatar, and the United Arab Emirates - Freer, C (2015)
This study, using contemporary history and empirical research, updates traditional rentier state theory, which largely fails to account for the existence of opposition movements, by demonstrating the political capital held by Muslim Brotherhood affiliates in Kuwait, Qatar, and the United Arab Emirates (UAE). This study thus also fills a critical gap in existing literature on political Islam by examining previously unstudied movements in the smaller Gulf states that do not require Brotherhood organisations to provide services, to form social networks, or to contest elections (aside from in Kuwait). Through a divergent case study, we demonstrate the degree to which and the means through which the Ikhwan shapes domestic politics in the some of the world’s wealthiest oil states, the super-rentiers. This research helps to break the causal link established by rentier state theory between oil rents and lack of politically relevant Islamist organizations. As will be shown, Muslim Brotherhood organizations in the Gulf are politically influential entities. It is important to note, however, that these groups shape cultural and social ideas as readily as political notions. The division between these sectors is often blurred in the atmosphere of the socially conservative super-rentiers, as politics is often displaced to the social sphere in restricted political systems. We therefore elucidate a new model for understanding how Muslim Brotherhood movements influence government policies, in addition to cultural and social policies, in the wealthiest rentier states of the Gulf, which we call rentier Islamism.